Foreign Consumers Purchasing Intention Towards Halal Product In Malaysia - Misnan, Misliyana Binti; Hee, Ong Choon; Rizal, Adriana Mohd (International Journal of Engineering and Technology, 2018)
Introduction: 'National Transformation 2050' or TN50 is an ingenuity to plan Malaysia's future in the 2020 to 2050. As of the viewpoint of becoming a developed nation, one of the TN50's agenda is to make our country one of the global halal supply chain which a part of economic growth for Malaysia. Halal food or halal product is the most important and potential sector to be the economic power for both domestic and globally.Aim: The aim of this paper is to provide a conceptual analysis of foreign consumer purchasing intention towards a few variable are halal integrity, halal awareness, halal certification, halal marketing and halal knowledge.Results: In this paper, conceptual analysis suggest that foreign consumer is an asset to generate national income in halal supply chain toward halal product.Research Implications: This paper supplies the theoretical implication and practical implication to understanding the relationships between halal variables and foreign purchasing intention.Paper type: Conceptual Paper